Penerapan Monitoring Locator Dies pada Perusahaan Stamping Part Otomotif - Denny Riandhita Arief Permana; Morgan Suseta; Ahlan Ismono (STMIK Budi Darma, 2022)
PT. Ganding Toolsindo is an automotive stamping parts company that has been established since 1998. This design is illustrated by conducting research at the kruing plant which is placed in the production division to assist the audit process at first and collect customer data, then get a mandate from the managerial to create an information system that is integration and innovation in the area of return and use of dies. Then look for accurate data with various methods so that the implementation of this system goes well, on this occasion the design was made with the concept of a dies locator information system that tracks the existence of dies for production and contains the identity of dies data in the production process. The problem that occurs is that the operator often places the dies not according to the existing shelves and in the end the dies become unorganized and neat when the production process is running. The method of developing this system is to use SDLC (system development life cycle), namely Waterfall. This information system uses mysql and codeigniter, then to run this system using xampp. The whole of this information system is about tracking the dies whether they are in production or on the shelf, if they are being repaired, the status of the dies will change as well as the status of the dies when they are being used in production. In this system feature there are customer data, part data, shelf data, user data and the duration of use of the dies. In the end, this system generates a report to the production supervisor to be seen and in what dies data is being used in production so that there will be no more misplaced shelves.